Goal-UML approach for modeling data warehouse requirements of Malaysian rural health care - Shafie, Sajaratul Huda; Ahmad, Azizah; Ta'a, Azman (2016)
Malaysian health care authorities in providing information system for rural communities required to meet up with the challenges, to provide informed decision-making by utilizes their enormous data.However, only a few of these initiatives have their success stories as many are still struggling to justify the investments such as Data Warehouse System (DWS).Among the most reason of the failures were that DWS requirements were overlooked, leading to poor DWS deployments. This paper attempts to model DWS requirements using goal-oriented and UML-based approach. DWS requirements for Rural health care were modeled two-folds: decision making requirements that centered on stakeholders; and focused on organizational and decisional aspects.The model can guide DWS development in the process and data needed in rural health care strategic decision-making.This provides new insights and facilitates the improvement of new health care knowledge